ADMINISTRATIVE REGULATION AS A MEANS TO PROVIDE ADMINISTRATIVE SERVICES IN UKRAINE - Legeza , Евгений Александрович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
Scientific article devoted to the concept of administrative regulations covering foreign experience of the Russian Federation to provide administrative services and more.